Variations in breastfeeding rates for very preterm infants between regions and neonatal units in Europe: results from the MOSAIC cohort. Issue 6 (10th June 2010) - Bonet, Mercedes; Blondel, Béatrice; Agostino, Rocco; Combier, Evelyne; Maier, Rolf F; Cuttini, Marina; Khoshnood, Babak; Zeitlin, Jennifer; ,
Abstract : Objectives: To compare breastfeeding rates at discharge for very preterm infants between European regions and neonatal units, and to identify characteristics associated with breast feeding using multilevel models. Methods: Population-based cohort of 3006 very preterm births (22–31 weeks of gestation) discharged home from neonatal units in eight European regions in 2003. Results: Breastfeeding rates varied from 19% in Burgundy to 70% in Lazio, and were correlated with national rates in the entire newborn population. Women were more likely to breast feed if they were older, primiparous and European; more premature, smaller and multiple babies or those with bronchopulmonary dysplasia were breast fed less. Variations across regions and neonatal units remained statistically significant after adjusting for maternal, infant and unit characteristics. Conclusion: It is possible to achieve high breastfeeding rates for very preterm infants, but rates varied widely across regions and neonatal units throughout Europe.